Women with Silenced Voices in the Novel Stigma by Hindhi Astina: a Psychoanalysis - Dania Dwi Lestari; Anas Ahmadi (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research was conducted to analyze the novel entitled "Stigma" by Hindhi Astina based on Sigmund Freud concept of Literary Psychology. This novel depicts aspects of life in the personality of the character Aralya Rylie Millano who faces mental pressure that is severe enough to result in excessive anxiety. This research aims to analyze how the structure of the Id, Ego, and Superego plays a role in describing a character's personality problems related to his mental condition and self-esteem. This research uses a qualitative descriptive method with the results of the research showing that the Id element in the character Aralya is seen in a strong desire to face repeated problems. The element of Ego can be seen in his actions which are influenced by fear due to the many threats and oppression he receives. Meanwhile, Superego can be seen in Aralya efforts to maintain her self-esteem by not showing weakness in front of the people around her. The character's self-defense attitude is driven by repression and the high hopes he places on someone. This theory can help understand the psychological dynamics of characters and the impact of traumatic experiences on the characters concerned.